O lugar geográfico em "beira rio beira vida" , de Assis Brasil - LIMA, Tiago Caminha de (2017)
To understand the multiple dynamics that take place in space it is necessary a dialogue among the numerous areas of knowledge. For this, it is necessary to understand the reality from the conditions by which they present themselves. In the relation between Geography and Literature one observes the valorization and the inter-relation of the geographic space from the experience of the man in the world through the daily life, situating his condition in the moment in which this one appropriates of the world, in the quotidian through experiences and feelings of belonging to the space. In order to do so, we try to answer the following question: How does the meaning of the geographical place stand out in the novel Beira Rio Beira Vida in the construction of the values and the identity of the characters, based on the experience acquired in the said space of the plot? Thus, it is emphasized that Literature through its works has a particular view of the world, not replacing other fields of knowledge, as well as the knowledge of Geography, and there must be a complement and appreciation of the dialogue between them. Starting from this premise, the present study envisages as a general objective: a) to analyze the meaning of the geographical place, expressed in the daily life of the characters of the Beira Rio Beira Vida literary work of Francisco de Assis Almeida Brasil, from the understanding of the articulation between the narrator, The characters, the quay and the plot of the literary work. The specific objectives are: a) To discuss the relation of the geographical place in the condition to situate the perspective of the human experience / experience; b) To understand the different forms of appropriation of the Geographical Place through the actions of the characters of the Beira Rio Beira Vida work; c) Describe the spatial identity expressed in the work of Assis Brasil, through the experiences lived by the characters, as well as the meaning of the geographical place present in this literary work. For this, the theoretical and methodological procedures of the research are based on the bibliographical survey of the works of Assis Brasil, an important foundation to base the literary in the geographic. This research was based on Tuan (1983), Holzer (1992), Claval (1999), Brosseau (2007), Correa and Rosendahl (2007), Marandola Junior (2009), Lívia de Oliveira ), Among other authors. The present analysis was carried out using the proposed content analysis method by Bardin (2011) regarding a set of communication analysis techniques aiming to obtain, by systematic and objective procedures for describing the content of messages, codes (quantitative or non-quantitative) that allow the inference of information regarding the conditions of production / reception of these messages. In this sense, the aforementioned novel stands out by the construction of the values and identity of the characters from the experience acquired in the mentioned space of the plot. This construction is closely related to the Beira Rio movement, especially to the quay, the main space for articulation of the characters in the work. The characters of this story are in Beira Vida, marginalized on the quay, seen by conservative society as a negative side of the city, as people unable to interrelate with other means and "trapped" to the environment of living on the quayside.